Pengaruh 2,4-Dichlorophenoxyacetic Acid (2,4-D) DAN Benzyl Amino Purine (BAP) Terhadap Induksi Kalus Dari Berbagai Jenis Eksplan Tanaman Duku (Lansium domesticum Corr.) - Mifta Ammaria Wulandari; Sherina Silva; Zaky Nuron Rizky; Jumiani Sarianti; Siti Zulaikha; Amin Nurokhman; Arif Yachya; Tutut Handayani; Syarifah; Dini Afriansyah (FMIPA : Universitas PGRI Adi Buana, 2022)
Lansium domesticum Corr. is called Duku, an endemic Indonesian plant whose fruit has commercial value. The formation of the seeds of this plant takes a relatively long time (±15 years) for conventional propagation. Micropropagation with plant tissue culture techniques can be a solution. In the first phase of micropropagation, optimization of the type and concentration of growth regulators for callus induction is needed. This study aimed to determine the response of various types of duku explants (such as leaves, petioles, and mother petioles) to combinations of growth regulators (such as 0 ppm 2,4-D + 0 ppm BAP; 0.75 ppm 2,4-D + 0, 5 ppm BAP; 0.75 ppm 2,4-D + 0.75 ppm BAP; 0.75 ppm 2,4-D + 1 ppm BAP) in callus induction. The explants were cultured on Wood Plant Medium (WPM) with 30 g sucrose and 8 g agar for 28 days. The results showed that the concentration of 0.75 2,4-D + 0.75 BAP with leaf stalk mother explants was the best for callus formation. The characteristics of the callus formed were white-yellow with a compact texture. Keywords : Lansium domesticum Corr., Callus induction, Growth regulators, Types of explants.